1994
DOI: 10.1021/bi00251a049
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of the thermal equilibria among lumirhodopsin, metarhodopsin I, and metarhodopsin II in chicken rhodopsin

Abstract: Using low-temperature time-resolved spectroscopy, we have directly observed thermal back reaction of metarhodopsin I (meta I) to lumirhodopsin (lumi) and that of metarhodopsin II (meta II) to meta I in chicken rhodopsin to demonstrate the presence of thermal equilibria among lumi, meta I, and meta II. The back reaction from meta I to lumi was observed when the rhodopsin sample irradiated at -35 degrees C was warmed to -20 degrees C, while that from meta II to meta I was observed when the sample irradiated at -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 29 publications
7
50
0
Order By: Relevance
“…Such an equilibrium had been proposed earlier," but data supporting that proposal were originally not very extensive. Recent evidence from low-temperature studies of chicken rhodopsin 96 (see below) have directly observed such an equilibrium, so this feature seems to be on secure ground. Further work will be required to determine which of the possible mechanisms prevails, however, since with only three observed rates the problem remains underdetermined for the number of microscopic rates in the possible mechanisms.…”
Section: Current Picture Ofmeta II Formationmentioning
confidence: 84%
“…Such an equilibrium had been proposed earlier," but data supporting that proposal were originally not very extensive. Recent evidence from low-temperature studies of chicken rhodopsin 96 (see below) have directly observed such an equilibrium, so this feature seems to be on secure ground. Further work will be required to determine which of the possible mechanisms prevails, however, since with only three observed rates the problem remains underdetermined for the number of microscopic rates in the possible mechanisms.…”
Section: Current Picture Ofmeta II Formationmentioning
confidence: 84%
“…Then the spectra (curves 2 (dotted curve) in C and D) containing only meta-I and meta-II were calculated by subtracting the spectra of residual 11-cis-pigments and photo-regenerated 9-cis-pigments from the spectra recorded. The amounts of 11-cis-and 9-cis-pigments were estimated by simulation of the measured spectra at the wavelength regions longer than 580 nm (or 560 nm in E122Q sample) with those of 11-cis-and 9-cis-pigments (26,51). The amounts of 11-cis-and 9-cis-pigments present in the illuminated WT sample were 41.8 and 4.0%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The pigment was regenerated by the addition of 2.5 nmol of 11-cis-retinal solubilized in ethanol (5 l) to each of opsin extracts (220 l of each). Then the pigment sample was subjected to low-temperature time-resolved spectroscopy to investigate formation and decay of meta II (29). The decay rate constants of meta II in native pigments were reported previously (11,15,30).…”
Section: Methodsmentioning
confidence: 99%